Pengaruh modal intelektual dan manajemen risiko terhadap kinerja keuangan pada perusahaan perbankan yang terdaftar di BEI tahun 2019-2022 - Sentika, Dena Nian; Yuliyanto, Agung; Muna, Arinal (Journal of Management and Digital Business, 2023)
Increasingly competitive competition and dynamic market conditions, as well as advances in increasingly sophisticated information technology, require banking companies to continue to innovate and improve their financial performance in terms of operational efficiency, better service, better risk management, and expanding the reach of financial services. This research examines the influence of intellectual capital and risk management on financial performance (ROA) in banking companies listed on the IDX in 2019-2022. This research uses secondary data in annual reports from banks listed on the IDX. The samples used were 92 from 23 companies with purposive sampling as a sampling technique. The data analysis method in this research is multiple regression analysis. This research shows that intellectual capital affects financial performance, and the risk management variable measured by liquidity risk has no effect on financial performance. In contrast, credit risk affects financial performance.